Repetitive Neonatal Erythropoietin and Melatonin Combinatorial Treatment Provides Sustained Repair of Functional Deficits in a Rat Model of Cerebral Palsy - Jantzie, Lauren L.; Oppong, Akosua Y.; Conteh, Fatu S.; Yellowhair, Tracylyn R.; Kim, Joshua; Fink, Gabrielle; Wolin, Adam R.; Northington, Frances J.; Robinson, Shenandoah (Frontiers in Neurology, 2018)
Cerebral palsy (CP) is the leading cause of motor impairment for children worldwide, and results from perinatal brain injury (PBI). To test novel therapeutics to mitigate deficits from PBI, we developed a rat model of extreme preterm birth (<28 weeks gestation) that mimics dual intrauterine injury from placental under-perfusion and chorioamnionitis. We hypothesized that a sustained postnatal treatment regimen that combines the endogenous neuroreparative agents erythropoietin (EPO) and melatonin (MLT) would mitigate molecular, sensorimotor, and cognitive abnormalities in adults rats following prenatal injury. On embryonic day 18 (E18), a laparotomy was performed in pregnant Sprague-Dawley rats. Uterine artery occlusion was performed for 60 minutes to induce placental insufficiency via transient systemic hypoxia-ischemia, followed by intra-amniotic injections of lipopolysaccharide, and laparotomy closure. On postnatal day 1(P1), approximately equivalent to 30 weeks gestation, injured rats were randomized to an extended EPO+MLT treatment regimen, or vehicle (sterile saline) from P1-P10. Behavioral assays were performed along an extended developmental time course (n=6-29). Open field testing shows injured rats exhibit hypermobility and disinhibition, and that combined neonatal EPO+MLT treatment repairs disinhibition in injured rats, while EPO alone does not. Furthermore, EPO+MLT normalizes hindlimb deficits, including, reduced paw area and paw pressure at peak stance, and elevated percent shared stance after prenatal injury. Injured rats had fewer social interactions than shams, and EPO+MLT normalized social drive. Touchscreen operant chamber testing of visual discrimination and reversal shows that EPO+MLT at least partially normalizes theses complex cognitive tasks. Together, these data indicate EPO+MLT can potentially repair multiple sensorimotor, cognitive, and behavioral realms following PBI, using highly translatable and sophisticated developmental testing platforms.